“Scottish Question” and Its New Cultural Meanings in “Culture Capitalism” by Alasdair Gray - E. A. Martynenko (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
An interpretation of the story “Culture Capitalism”, placed in the authoritative anthology “Every Short Story: from 1951 to 2012” of the classic of Scottish literature Alasdair Gray, in the context of the original interpretation by the patriotic writer of the “Scottish question «is offered in the article. It is noted that the problems of the story, written in 1990, are closely related to the establishment in the same year of the status of Glasgow as a cultural capital. Gray’s doubt about the declared cultural messages is analyzed through the prism of the concepts of P. Bourdieu and S. Žižek. It is proved that certain plots and images indicate the development in Gray’s work of ideas close to researchers of postcolonial literature, and in particular the idea of “internal colonization" of Scotland. An interpretation of a number of images that have an allegorical meaning in the light of criticism of English cultural, political and economic hegemony is offered in the article. In addition, based on the ideas of J. Homberg-Schramm about the nature of the nation’s ideas about its gender, class and linguistic identity, the author considers the representation of national auto-stereotypes and their consistent revision. The author concludes that Alasdair Gray sees the possible peaceful coexistence of England and Scotland beyond the boundaries of the model of exploitative colonialism.